Mlipir: The Genesis within Relations of Production between Industrial Sector and Rural Society - Utama, Rahardika Arista (UI Scholars Hub, 2013)
This paper examines how the interactions between industrial development actors in rural setting reflect the internal dynamics of Third World countries that maintain dependence on developed countries. The diverse discussion on the impact of industrialization which mostly emphasized on particular issues is difficult to depict the comprehensive situation on the impacted society. Further analysis which recognized the existence of the mutual relations among state, market, and society is necessary to best describe the invisible but essential impact of industrialization. Thus, this paper argues that inequality is the essential impact of industrialization which has been emerged in various form of social system as the consequences of the relation of production between local elites and market economy actors in all level of development. Through analyzing the case of particular system of production called mlipir system which emerged and perpetuated within relations of production in the plywood industrial development area, the study found that the interactions of national actors and local actors who have aligned interests with the global imperialism have perpetuated particular group of people who remain in poverty despite actively conduct production activities.